BRAND DEVELOPMENT MANAGEMENT IN SOCIAL NETWORKS - TANASIICHUK, Alona; HROMOVA, Olha; KRUPSKYI, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the study of the process of managing brand development in social networks, it was determined that an effective strategy of using social networks to build and develop a brand will increase its recognition and attract new customers. The study confirmed the importance of creating interesting and relevant content, interacting with the audience through responses to comments and discussions, as well as an active presence on various social media platforms. In the research process, it was established that the analysis and consideration of previous campaigns in relevant social networks helps to increase the effectiveness of future brand management strategies. Methods of measuring the results of brand development management in social networks have been determined for further improvement of strategies. Creating a brand strategy that defines the brand’s mission, values and goals on social media platforms has been proven to be very important to any business with numerous benefits, a. creating segments of the interested audience and developing a strategy to attract them to the brand will help increase business efficiency, increase competitiveness and increase the profitability of the enterprise. It is well-founded that planning a content calendar is an important component of a content strategy, as it allows you to systematize the placement of content on various platforms and communication channels. This plan helps to ensure the constant availability of interesting and useful content for the audience, increases the confidence of information about the brand and helps to build long-term relationships with customers, is crucial for the successful communication of the brand with the audience and increasing its recognition and authority. It has been proven that the combination of various strategies to achieve the maximum effect in the development of the brand in social networks is an important aspect, since the combination of content marketing, interaction with the audience, advertising and visual content will significantly increase the effectiveness of the strategy in social networks. The study proposed a classification of brand development strategies in social networks, systematized indicators of brand account analysis on popular platforms, systematized measurable goals, indicators, metrics for evaluating branding strategies in social networks, characteristics of social network analytics tools for measuring these indicators.